Topography-dependent paradox: how extreme climate and the digital economy affect food security differently across terrains - Zheng, Xinyue; Wang, Siyu; Sun, Zhixian; Xin, Xiaohui (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe increasing frequency of extreme weather events poses significant challenges to global food security, while the rapid development of the digital economy offers new pathways for mitigation.MethodsThis study constructs a Household Food Insecurity Experience Scale and a Digital Economy Indicator System based on survey data from 1,066 households in Sichuan Province, China, collected in 2024. Using publicly available extreme weather data from official websites, the research examines the impact of extreme weather on farmers’ food security across different terrains and explores the moderating role of the digital economy.ResultsContrary to conventional understanding, an increase in the extreme weather index was found to enhance household food security, with the effect varying by topography. In plain areas, where extreme weather events occur more frequently, households exhibited higher food security indices compared to non-plain areas. Specifically, a one-unit increase in the extreme weather index raised the food security index by 28.2% in plain areas but reduced it by 9.7% in non-plain areas. This divergence stems from differences in food access mechanisms shaped by terrain. In plains, extreme weather increased households’ reliance on external food purchases without significantly compromising self-sufficiency. In contrast, in non-plain areas, extreme weather substantially weakened self-sufficiency, while complex terrain further restricted access to external food supplies. Moreover, the digital economy effectively mitigated the negative impact of extreme weather on food security in topographically disadvantaged regions. Under its moderating influence, a one-unit increase in the extreme weather index amplified the food security improvement in plain areas from 28.2 to 68.9%, while in non-plain areas, extreme weather no longer exerted a significant effect. The underlying mechanism lies in the digital economy’s ability to enhance agricultural insurance participation, food production efficiency, and household income, collectively offsetting extreme weather’s adverse effects through increased earnings, reduced production costs, and better risk management.ConclusionThis study highlights the terrain-dependent effects of extreme weather on household food security and the moderating role of the digital economy. The findings provide valuable insights for policymakers and stakeholders to strategically leverage digital economy practices in narrowing regional disparities in food security.